2019
DOI: 10.7554/elife.48264
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory muscarinic acetylcholine receptors enhance aversive olfactory learning in adult Drosophila

Abstract: Olfactory associative learning in Drosophila is mediated by synaptic plasticity between the Kenyon cells of the mushroom body and their output neurons. Both Kenyon cells and their inputs from projection neurons are cholinergic, yet little is known about the physiological function of muscarinic acetylcholine receptors in learning in adult flies. Here, we show that aversive olfactory learning in adult flies requires type A muscarinic acetylcholine receptors (mAChR-A), particularly in the gamma subtype of Kenyon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 89 publications
0
39
1
Order By: Relevance
“…Perhaps, there exist a greater number of mAChRs near the synapse than on the soma of MB296B DANs. For example, mAChRs are also present on the processes of Kenyon cells in the mushroom body ( Bielopolski et al, 2019 ; Kondo et al, 2020 ) and form a tripartite synapse with dendrites from MB output neurons (MB-ONs) and axonal processes of MB296B DANs. Although requirement for the IP 3 R and the mAChR was restricted to 48–96 hr APF, these data suggest that the neurotransmitter acetylcholine stimulates dopamine release in adult DANs through mAChR-IP 3 R signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, there exist a greater number of mAChRs near the synapse than on the soma of MB296B DANs. For example, mAChRs are also present on the processes of Kenyon cells in the mushroom body ( Bielopolski et al, 2019 ; Kondo et al, 2020 ) and form a tripartite synapse with dendrites from MB output neurons (MB-ONs) and axonal processes of MB296B DANs. Although requirement for the IP 3 R and the mAChR was restricted to 48–96 hr APF, these data suggest that the neurotransmitter acetylcholine stimulates dopamine release in adult DANs through mAChR-IP 3 R signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Motion correction was carried out as in Bielopolski et al, 2019 ; Lin et al, 2014 ; flies with excessive uncorrectable motion were discarded. For experiments without 3D-skeletonization (see below), ΔF/F was calculated in ImageJ for manually drawn regions of interest (ROIs).…”
Section: Methodsmentioning
confidence: 99%
“…Glutamate for instance is mainly excitatory, however, in invertebrates it can also have inhibitory effects when it acts on a glutamate-gated chloride channel, known as GluClα ( Cully et al, 1996 ; Liu and Wilson, 2013 ; Mauss et al, 2015 ). Recently, it has also been shown that acetylcholine, usually excitatory, might also be inhibitory in Drosophila , if it binds to the muscarinic mAChR-A receptor ( Bielopolski et al, 2019 ). Hence, knowledge inferring the type of transmitter receptor at a synapse is essential for our understanding of the way neural circuits process information.…”
Section: Introductionmentioning
confidence: 99%